2011
DOI: 10.1140/epjb/e2010-10553-6
|View full text |Cite
|
Sign up to set email alerts
|

Goos-Hänchen-like shifts for Dirac fermions in monolayer graphene barrier

Abstract: We investigate the Goos-Hänchen-like shifts for Dirac fermions in transmission through a monolayer graphene barrier. The lateral shifts, as the functions of the barrier's width and the incidence angle, can be negative and positive in Klein tunneling and classical motion, respectively. Due to their relations to the transmission gap, the lateral shifts can be enhanced by the transmission resonances when the incidence angle is less than the critical angle for total reflection, while their magnitudes become only t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 43 publications
9
82
1
Order By: Relevance
“…Like single and double barrier structures, the transmission is bilaterally symmetrical with respect to the normal incidence. In addition, we notice that as observed in [20,23], the GH shifts are related to the transmission gap around the two Dirac points. Now, we will turn to discus the influence of the gap and the width d B = d W on the transmission for graphene SLs.…”
Section: Graphene Superlatticessupporting
confidence: 62%
See 2 more Smart Citations
“…Like single and double barrier structures, the transmission is bilaterally symmetrical with respect to the normal incidence. In addition, we notice that as observed in [20,23], the GH shifts are related to the transmission gap around the two Dirac points. Now, we will turn to discus the influence of the gap and the width d B = d W on the transmission for graphene SLs.…”
Section: Graphene Superlatticessupporting
confidence: 62%
“…Recently, interesting results were reported on the quantum GH shift for charge carriers in graphene systems [20][21][22][23]. This does not only reflects the unique transport properties of Dirac electrons and holes in graphene nanostructures, but also promotes the application of graphene nanostructure in nanoelectronic devices.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Different from the GH shifts in graphene barrier, the GH shifts in double barrier structure can be greatly enhanced [53] inside the transmission gap in a single barrier [52,79]. This giant GH shift is attributed to the quasibound states formed in double barriers.…”
Section: Single Double and Multiple Barriersmentioning
confidence: 91%
“…The latter has been studied at a single graphene interface [8,9] and in graphene-based electric and magnetic potential barriers [10]. Subsequently, it was shown that the modulation of Goos-Hänchen like (GHL) shifts can be controlled by varying the electrostatic potential and induced gap [11] and can even be enhanced by transmission resonances. Very recently, the giant GHL shifts for electron beams tunneling through graphene double barrier structures [12] was also investigated and it was found that the shifts exhibits a sharp peaks inside the transmission gap.…”
Section: Introductionmentioning
confidence: 99%